Reflexões acerca do uso do Khan Academy para o ensino de semelhança de triângulos em aulas remotas - Konzen, Sandra (2020)
With this academic work we seek to promote reflections about the use of the Khan Academy platform for teaching Triangle Similarity in remote classes. Therefore, we prepared a pedagogical proposal implemented in a class of the 9th grade of Elementary School in a state school in the municipality of Maravilha-SC. The methodology and digital technological resources were chosen with the objective of inserting digital technologies in Mathematics classes, as well as assisting in the development of remote classes. After implementing this methodology, we analyzed the practice and also sought to investigate what are the strengths and weaknesses of using the Khan Academy application combined with the Flipped Classroom methodology for teaching Triangle Similarity, through remote classes. One of the difficulties observed is in relation to the students' adhesion to remote classes and even some students who joined ended up not sending all the activities developed, as well as we felt the need for more synchronous classes. On the other hand, the Khan Academy platforms proved to be quite efficient for their use in remote education, having several functionalities, being complete in relation to the contents offered and also having options for each student to follow their study pace, as well as pausing the videos and watch as many times as necessary. Still, about Google Classroom, it has several potentialities, being very useful for its use in remote classes. Finally, in relation to Meaningful Learning, we have not been able to go into this topic much further, although there are beginnings that have occurred, in some cases, when we compare the history of the development of these activities.